2021
DOI: 10.3889/oamjms.2021.6048
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Supplementation as an Adjuvant Therapy Potentially Increase Serum Superoxide Dismutase Levels in Acne Vulgaris Patients

Abstract: BACKGROUND: Acne vulgaris (AV) is a chronic inflammatory disease in the pilosebaceous unit. Recent research has begun to focus on the essential relationship between oxidative stress and the pathogenesis of AV. The use of antioxidants like coenzyme Q10 (CoQ10) that has various advantages as adjuvant therapy is expected to be beneficial for AV. AIM: The study was aimed to analyze the effect of CoQ10 supplementation on serum SOD levels and the severity of AV patients. METHODS: A double blind-randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Of these, 2489 records were excluded based on title and abstract screening. Among 93 full-text articles assessed for eligibility, 42 articles (3346 participants) met the inclusion criteria and were included in the review (Figure). Of the included studies, 27 (64.3%) were of poor quality, 11 (26.2%) were of fair quality, and 4 (9.5%) were of good quality (Table 1, Table 2, and Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 2489 records were excluded based on title and abstract screening. Among 93 full-text articles assessed for eligibility, 42 articles (3346 participants) met the inclusion criteria and were included in the review (Figure). Of the included studies, 27 (64.3%) were of poor quality, 11 (26.2%) were of fair quality, and 4 (9.5%) were of good quality (Table 1, Table 2, and Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Among 93 full-text articles assessed for eligibility, 42 articles (3346 participants) met the inclusion criteria and were included in the review (Figure). Of the included studies, 27 (64.3%) were of poor quality, 11 (26.2%) were of fair quality, and 4 (9.5%) were of good quality (Table 1, Table 2, and Table 3). Detailed information on the included studies, including for poor-quality studies, is available in the eTable in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…58 In this sense, some adjuvant therapies that aim to increase SOD serum levels through coenzyme Q10 supplementation for example have been used to treat acne. 33 There is no consensus on skin and blood SOD levels in vitiligo patients. A group in India reported that significantly high SOD levels were observed in active vitiligo patients compared with stable vitiligo and healthy controls.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…Antioxidant enzymes have been widely studied to treat skin diseases as skin cancer, 28 vitiligo, 29 ageing‐related injuries, 30 psoriasis, 31 rosacea 32 and acne, 33 among others. Figure 1 illustrates a schematic representation of the general mechanism of action of antioxidant enzymes with dermatological potential.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation